Implementing The Role of NGOs In Curricular and Societal Civic Education Through Political Literacy - Anjarsari, Riya; Rusnaini, Rusnaini; Nuryadi, Muhammad Hendri (Research Synergy Foundation, 2023)
The importance of political literacy in this context NGOs have the potential to contribute to developing political literacy that is more effective and has a wider impact. Although Civic Education is an integral part of the curriculum, the challenge of teaching democratic values and effective political participation can still be implemented by NGOs as a form of curricular and societal Civic Education. The research in this paper aims to find out the role of NGOs related to political literacy in society through education and advocacy strategies. The research method used is qualitative, with data collection techniques of observation, documentation, and structured, open, and in-depth interviews with representative civic education teachers and representative staff of local NGOs as informants selected by purposive sampling. The findings were based on research conducted for six months with limitations in regional coverage. The political literacy program was declared successful in demonstrating the role of NGOs with the strategy of conducting political literacy training, providing easy-to-understand political information, holding public discussions, inviting people to get involved in the political process, and establishing partnerships with government institutions and civil society. Political literacy activities have a positive impact on participants, although it is not seen and felt directly by the entire community. In conclusion, through political literacy, NGOs can help people become politically literate, less susceptible to political issues, and more open in their political thoughts and actions.